Morphological analysis of cold-water coral skeletons for evaluating in silico mechanical models of reef-scale crumbling - Peña Fernández, Marta; Williams, Josh; Büscher, Janina V.; Roberts, J. Murray; Hennige, Sebastian J.; Wolfram, Uwe (Frontiers in Marine Science, 2025)
The structural complexity of cold-water corals is threatened by ocean acidification. Increased porosity and thinning in structurally critical parts of the reef framework may lead to rapid physical collapse on an ecosystem scale, reducing their potential for biodiversity support. Understanding the structural-mechanical relationships of reef-forming corals is important to enable the use of in silico mechanical models as predictive tools that allow us to determine risk and timescales of reef collapse. Here, we analyze morphological variations of the branching architecture of the cold-water coral species Lophelia pertusa to advance mechanical in silico models based on their skeletal structure. We identified a critical size of five interbranch lengths that allows using homogenized finite element models to analyze mechanical competence. At smaller length scales, mechanical surrogate models need to explicitly account for the statistical morphological differences in the skeletal structure. We showed large morphological variations between fragments of L. pertusa colonies and branches, as well as dead and live skeletal fragments which are driven by growth and adaptation to environmental stressors, with no clear branching-specific patterns. Future in silico mechanical models should statistically model these variations to be used as monitoring tools for predicting risk of cold-water coral reefs crumbling.